EVALUATION OF THE EFFICIENCY OF THE SOCKET LATCHES BY TURN-LINK DIAPHRAGMS USING THE CFD-PACKET - Usaty, Alexander; Pham, Anh Tuan (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2018)
ABSTRACT As a result of conducting and processing the results of numerical studies, an analytical dependence was obtained to estimate the squares of the velocity coefficients of the nozzle arrays with Rotating diaphragms. The obtained dependence makes it possible to estimate the effect of the geometric and regime parameters of the gratings on their efficiency. To obtain such a dependence using the rich Rechtshafner plan and an additional plan that increases the accuracy and adequacy of the dependence, a computational experiment was planned. In accordance with the developed experiment plans, a number of nozzle arrays with different geometries and the relative displacement of their fixed and Rotating parts were designed and their calculated areas were constructed. With the help of complex CFD, the corresponding computational studies were carried out to evaluate the effect of geometric and regime parameters of nozzle arrays with Rotating diaphragms on their effectiveness. The squares of the velocity coefficients of the nozzle arrays with Rotating diaphragms obtained in the course of numerical studies were used in the process of appropriate processing and the creation of an analytic dependence to evaluate the effectiveness of such gratings. The results of numerical studies, the form of the analytical dependence and the graphs of the influence of geometric and regime parameters on the squares of the speed coefficients of the nozzle arrays with Rotating diaphragms are presented. The obtained dependence is intended for solving problems of synthesis and analysis of heating turbines with adjustable steam samplings.